2007
DOI: 10.2106/jbjs.f.00226
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Scapular Notching in Patients Managed with the Delta III Reverse Total Shoulder Replacement

Abstract: Inferior scapular notching after reverse total shoulder arthroplasty adversely affects the intermediate-term clinical outcome. It can be prevented by optimal positioning of the glenoid component.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
285
6
27

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 450 publications
(334 citation statements)
references
References 9 publications
16
285
6
27
Order By: Relevance
“…Inferior scapular notching is a frequent complication associated with reverse shoulder arthroplasty [4,6,8,[11][12][13][14][15][16]. Sirveaux et al [4] found scapular notching in 49 of 77 patients (63.6 %) at a mean follow-up of 44.5 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inferior scapular notching is a frequent complication associated with reverse shoulder arthroplasty [4,6,8,[11][12][13][14][15][16]. Sirveaux et al [4] found scapular notching in 49 of 77 patients (63.6 %) at a mean follow-up of 44.5 months.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that mild or moderate scapular notching may have few or no clinical implications in the short-or medium-term following implantation. However, the long-term effects are unclear, and thus there is concern over the possibility that severe notching may jeopardise the stability of the glenoid component and affect the functional outcome [6,8]. Several attempts have been made to reduce the incidence of this drawback by changing the position of the metaglene or conceiving new prosthetic designs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that scapular notching is the most regular complication associated with RSP (39). Also, it is suggested that scapular notching is due to the prosthesis design.…”
Section: Scapular Notchingmentioning
confidence: 99%
“…In recent years, RTSA models have gained popularity and seem to currently boast the best functional outcome [18,21,38,39], since this prosthetic design enables a distalisation and medialisation of the prosthetic centre of rotation [10,19,20]. However, notching with consecutive glenoid loosening, instability and infection are still common problems in this prosthetic design [4,15,30,36,40].…”
Section: Introductionmentioning
confidence: 99%